Jejak Digital Ke Keputusan Pembelian: Peran Media Sosial, Electronic Word of Mouth (EWOM), dan Keyakinan pada Wisatawan Generasi Y di Jawa Tengah [Digital Footprint to Purchase Decisions: The Role of Social Media, Electronic Word of Mouth (EWOM), and Confidence in Generation Y Travelers in Central Java] - Larosa, Tafati Linia (Indonesian Marketing Journal, 2025)
One phenomenon that has emerged after the COVID-19 pandemic is the tourists now tend to use internet technology to plan their trips and book hotels. This change is a new challenge in the hospitality sector where the hotel management must continue to innovate and follow technological developments used by its customers. This study aimed to determine the effect of using social media and electronic word of mouth on purchasing decisions and the role of beliefs that mediate the impact of using social media and electronic word of mouth on purchasing decisions. This research was conducted in Central Java province by distributing questionnaires to tourists who stayed at hotels in Central Java and made hotel reservations through online travel agents (OTA). Questionnaires that have been tested for validity and reliability are addressed to 100 respondents. The data collection method uses online questionnaires, literature, observation, and interviews. While the measurement of data analysis using Partial Least Square (PLS). The results of the data analysis obtained are: The use of social media and electronic word of mouth has a positive and significant effect on purchasing decisions (hotels booking) in Central Java by Y generation tourists, directly or mediated by conviction. Findings inform hotels, OTAs, and tourism authorities that EWOM strengthens consumer conviction and increases hotel bookings. Abstrak Bahasa Indonesia: Salah satu fenomena yang terjadi pasca pandemic COVID-19 yaitu wisatawan kini cenderung menggunakan teknologi internet dalam merencanakan perjalanan wisatanya, termasuk untuk memesan hotel. Perubahan ini menjadi tantangan baru di bidang perhotelan di mana pihak manajemen hotel harus terus berinovasi dan mengikuti perkembangan teknologi yang dipakai oleh para konsumennya. Tujuan dalam penelitian ini ialah untuk mengetahui pengaruh penggunaan media sosial dan electronic word of mouth terhadap keputusan pembelian dan peran keyakinan yang memediasi pengaruh penggunaan media sosial dan electronic word of mouth terhadap keputusan pembelian. Riset ini diadakan pada area provinsi Jawa Tengah dengan menyebar kuesioner kepada wisatawan yang pernah menginap di hotel-hotel di Jawa Tengah dan melakukan pemesanan hotel melalui online travel agent (OTA). Kuesioner yang telah sudah diuji validitas dan reliabilitasnya ditujukan kepada 100 responden. Cara pengumpulan datanya memakai kuisioner online, kepustakaan, observasi, dan wawancara. Sedangkan pengukuran analisis datanya menggunakan Partial Least Square (PLS). Hasil analisi data yang diperoleh yaitu penggunaan sosial media dan electronic word of mouth berpengaruh positif dan signifikan pada keputusan pembelian (pemesanan) hotel di Jawa tengah pada wisatawan generasi Y baik secara langsung maupun dimediasi oleh keyakinan. Hasil dari penelitian ini diharapkan dapat memberi padangan bagi hotel, OTA, dan Dinas Pariwisata tentang pentingnya electronic word of mouth untuk meningkatkan kepercayaan konsumen serta meningkatkan keputusan pembelian.